Karakteristik Fisikokimia dan Sensori Selai Lembaran Albedo Semangka (Citrullus lanatus.) dengan Substitusi Daging Buah Cempedak - Rosy Hutami; Sultan Guna Wibawa; Intan Kusumaningrum; Lia Amalia; Distya Riski Hapsari; Siti Nurhalimah (JURNAL AGROINDUSTRI HALAL, 2024)
Sheet jam is a processed jam food product that is processed with the addition of hydrocolloid so that it has a semi-solid, plastic and non-sticky texture. This study aims to utilize the watermelon rind and chempedak fruit in the manufature of sheet jam as one of the food diversifications. This studi used a one-faktor Completely Randomizd Design (CRD), namely the comparison of the watermelon rind and chempedak fruit flesh with 3 treatment levels (50%:50%, 60%:40%, 70%:30%). Data analysis used ANOVA with Duncan's Advanced Test at 95% confidence interval. The analysis used included chemical test analysis (moistur content, ash content, pectin content, crude fiber content), physical tests (total dissolved solids and color test), sensory quality, and hedonic tests to determine the product with the best treatment. The best treatment of sheet jam was with a ratio of 50% watermelon rind and 50% puree of chempedak pulp, having a moistures content of 19.83%, ash content of 0.42%, pectin content of 3.23%, crude fiber of 2.92%, and TDS 21.8 % °Brix. The results of the sensory quality of sheet jam with the best treatment had a brownish yellow color, tended to be sweet, smelled of less strong watermelon albedo, had a strong aroma of chempedak, and quite springy in texture. The results of the hedonik test on sheet jam were the best for color, aroma, taste, texture, and Overall parameters in the direction of liking (6,42 – 7,30).